Applying standard competency assessment in vocational teaching practices - Mohamad, Mimi Mohaffyza; Abu Bakar, Nabilah; Sulaiman, Nor Lisa; Mohd Salleh, Kahirol; Lai, Che Sern (Canadian Center of Science and Education, 2015)
Teaching in vocational education is focused on knowledge and skills. Psychomotor is an aspect that emphasized in teaching competency in vocational education. Teaching based on psychomotor is a way to provide students with the hands on skills. Teachers are the main character in the teaching session. Therefore, this paper explained the differences among teachers in teaching based Standard Competency Assessment with their expertise in particular field. Research used survey design involved 301 teachers from Vocational Colleges specifically teaching practical task in Technology Courses. The focused elements are experienced and qualification of expertise based on recognition by Malaysia Skill Certification. Result showed that there are differences in the application of the teaching methods between experienced and inexperienced instructors teaching at the workshop from the teaching and evaluation aspects. The skills certificates ownership by the instructors shows differences in the aspects of teaching methods compared to the teaching implementation. In summary, teachers or instructors who teaching in vocational courses need the basic requirement especially skills recognition to fulfill competency assessment.